2018
DOI: 10.1182/blood-2018-05-846592
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oral anticoagulants with vitamin K epoxide reductase in its native milieu

Abstract: Key Points Acenocoumarol is the most efficient oral anticoagulant with the least variation of resistance among naturally occurring VKOR mutations. Warfarin and fluindione are equipotent for anticoagulation control but have different mechanisms of action on VKOR inactivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 60 publications
2
29
0
1
Order By: Relevance
“…Therefore, warfarin should be competitive with substrates at the PO state, but not competitive at the O or R states. This difference explains the previous observation that warfarin is a mixed inhibitor showing a combination of noncompetitive and competitive kinetics (15,16).…”
Section: Discussionmentioning
confidence: 51%
“…Therefore, warfarin should be competitive with substrates at the PO state, but not competitive at the O or R states. This difference explains the previous observation that warfarin is a mixed inhibitor showing a combination of noncompetitive and competitive kinetics (15,16).…”
Section: Discussionmentioning
confidence: 51%
“…As shown in Table S1, there were two exceptions to this rule. For study NCT02546167 (CART-BCMA UPenn), we decided to use the full publication [ 20 ] rather than the meeting abstract [ 21 ]. For study NCT03661554 (BCMA nanoantibody), the latest publication involving 16 CAR-T-infused patients was not considered because outcome data were incompletely reported (only for 7 patients) [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…A subsequent evaluation showed that the ( S )‐enantiomer of COT‐warfarin was four‐fold more potent than the ( R )‐enantiomer (see the Supporting Information, Figure S5). Considering that the genetic variation in the VKOR gene is one of the largest factors contributing to the difficulty in the clinical use of warfarin, the performance of the racemic COT analogue ( 8 ) was explored against the 27 naturally occurring human VKOR mutants by using VKOR/VKORC1L1 double gene knockout reporter cells ,. It was found that 8 and warfarin displayed a similar pattern of resistance to all naturally occurring VKOR mutants, suggesting they might bind to the same site in VKOR.…”
Section: Methodsmentioning
confidence: 99%